Analysis of the Double Head Streamer Discharge Simulation under Different Pressures - Maha .F. Abdulameer; Thamer H. Khalaf (Iraqi Journal of Physics)
In this research, the dynamics of double-head streamer discharge initiation, propagation, interaction and breakdown in the air under different pressure values were presented. The double-head streamer discharge dynamics were analysed within a plane-to-plane electrode configuration. That was done through many aspects proposed, such as electron density, electric field, space charge density and streamer propagation speed. The simulation performed using ‘COMSOL Multiphysics’ is based on the finite element method and was carried out with the fluid model. The fluid model describes the movement of particle concentrations using partial differential equations (PDEs) together with Poisson’s equation; Poisson's equation and charge concentrations determine the electric field distribution in space. According to the results, as the pressure increased from (1, 2 and 3atm), the evolution time of the streamer increased from (0.563 to16.29ns) with the same breakdown voltage of 19kV. This means that the double-head streamer discharge developed faster with the decrease in pressure.